Conversion of glucose into levulinic acid in continuous segmented turbulent flow with enhanced chemical reaction. (14th September 2021) - Lau, Kam Sheng; Chin, Siew Xian; Jaafar, Sharifah Nabihah Syed; Chia, Chin Hua
Graphical abstract: Abstract: Fine chemicals derived from renewable carbon feedstocks can be potentially used as various platform chemicals in the production of fuel additives, polymers, green solvents, foods, and cosmetics. Batch reactions are widely used for the conversion of lignocellulosic biomass into fine chemicals, which possess several drawbacks. Therefore, we investigated the conversion of glucose into various fine chemicals using a segmented (plug) flow reaction system with different segment lengths. The highest conversion of glucose (67.3%) and reaction yield of formic acid (75.1%), levulinic acid (68.9%), and 5-hydroxyl methylfurfural (0.49%) were obtained using reaction conditions of 1 g/L glucose solution and 0.25 M H2 SO4 at 150 °C for a short segment reaction. Higher glucose conversion was observed with shorter segments as the result of internal mixing, which enhanced the chemical reactions.